PENGARUH KOMPOSISI MEDIA TANAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (lpomea reptans poir) - Ahmad Ahmad; Sunawan Sunawan; Agus Sugianto (AGRONISMA, 2021)
In increasing the productivity of vegetable crops or land spinach, it can be done by providing planting media or organic fertilizers and NPK fertilizers. This study aims to determine the effect of differences in planting media consisting of soil, sand, and compost with a dose of NPK fertilizer.Â The research was carried out at the Green house of the Faculty of Agriculture, Islamic University of Malang, Lowokwaru District, Malang City, with an altitude between 440-667 m asl, temperatures ranging from 22.9 Â° C-25.8 Â° C, rainfall reached an average ranged from 1,800-3,000 mm per year, the research was conducted on 2 October-8 November 2019. The experiment used a 2 factorial completely randomized design method (CRD). The experimental treatment was a combination of the composition of the planting medium and the dosage of NPK fertilizer. The combination of planting media, namely: M1: soil = 50%, sand = 25%, compost = 25%. M2: soil = 25%, sand = 50%, and compost = 25%. M3 = soil = 25%, sand = 25%, and compost = 50%. The dosage of NPK fertilizer D0 = tamapa fertilizer, D1 = 1.5 grams, D2 = 3 grams, D3 = 2.25 grams, and D4 = 4.5 grams on kale plants. The results showed that the treatment of the composition of the planting medium and the dosage of NPK fertilizer increased the yields on plant height at the age of 28 DAS and 31 DAS, and the NPK fertilizer dose had a significant effect on the number of leaves and leaf area and was significantly different from other treatments.